Value in the eyes of users: a case study of web-based applications using repertory grid technique - Madi, Tamer; Dahalin, Zulkhairi; Baharom, Fauziah (2018)
A few years ago, users were solely end-consumers with very limited knowledge and role. While today they are a common element in the development of any product or service with a fruitful knowledge and active role. Identifying the values and needs of the user constitutes a crucial activity in the development process. However, values are still implicit and inexpressive. Models and techniques which incorporate user value in the development process are still missing so far. Therefore, the objective of this paper is to understand the values and activities that lead to its creation from the point of view of users. The Repertory Grid Technique (RGT) has been employed where (22) users have been interviewed to derive their values and activities in web-based applications. The results show that the values related to everyday life activities are the most important to the user while values related to the design of the web application come second in terms of importance. The results also show that the most important activities to the user are those activities for learning, networking and sharing. The findings indicate that there is a strong linkage between user value and the concept of user experience which require to be explored further and considered in any new development projects.